MAPPING OF CORAL REEF DISTRIBUTION USING THE LYZENGA ALGORITHM METHOD WITH SENTINEL-2 IMAGERY IN PASUMPAHAN ISLAND - Jenny Lisiana; Mubarak Mubarak; Thamrin Thamrin; Zulkifli Zulkifli; Ilham Ilahi (Asian Journal of Aquatic Sciences, 2026)
The coral reef ecosystem on Pasumpahan Island holds significant ecological and economic value but is vulnerable to environmental pressures. This study aims to map shallow-water benthic habitats and to assess the accuracy of Sentinel-2 satellite image classification using the Lyzenga water-column correction method. The research involved radiometric correction, application of the water-column correction algorithm, and supervised classification using the Maximum Likelihood algorithm. Field validation was conducted using 30 ground-check points to assess accuracy using a confusion matrix. The analysis results indicate that the shallow waters of Pasumpahan Island are dominated by the substrate class, covering 15.75 Ha, while the coral reef class covers 7.78 Ha. The accuracy assessment yielded an Overall Accuracy of 83.3% and a Kappa Coefficient of 0.67, indicating substantial agreement and confirming the method's validity for spatial mapping. This study concludes that the Lyzenga method is effective in mapping benthic habitats with adequate accuracy, and the resulting map can serve as baseline data for area managers for conservation zoning.